Scenic science of the national parks : an explorer's guide to wildlife, geology, and botany - Hoff, Emily, 1986-; Keller, Maygen, 1986- (Ten Speed Press, 2020)
"Discover a fresh perspective on America's National Parks in a stunning illustrated guide featuring fascinating science, fun trivia, and helpful insider travel tips for all sixty parks. What caused the stone arches in Arches National Park? Why are Yellowstone's geothermal pools such wild colors? How did the Badlands get their name? America's sixty National Parks are some of the most beautiful unique, and biodiverse places on earth, and are visited by millions annually. Home to some of our most treasured species of animals and plants, as well as some of the most striking geological features--like mountains, rock arches, caves, volcanoes, and geysers--the parks are also scientific playgrounds, where visitors can learn about botany, geology, and wildlife first hand. Scenic Science of the National Parks curates and breaks down the most compelling natural science highlights of each park, from volcanic activity, glaciers, and coral reefs to ancient redwood groves, herds of bison, giant bats, and beyond. Highlighting information on the history and notable features of each park, as well as cool insider travel tips vetted by National Park Service park rangers, this book makes a fun addition to any park lover's book collection"--